Clarice Lispector e a literatura Brasileira no mapa literário Europeu - Machado Garcia Arf, Lucilene [UNESP] (My University, 2011)
This small inventary of the Brazilian literary production in Europe, propelled by the string presence of Clarice Lispector, shows how Brazilian literature, formerly known as being close to orality and linked to a sociological reality, is now appreciated thanks to its aesthetic features. Lispector's work is built on human language and relationships, as well as the feminine soul; her work will penetrate the European elite -including the Spanish one.
Clarice Lispector and the Brazilian literature in the European literary context
Keywords: Brazilian literature; Clarice lispector; European cultural elite